49.8k views
5 votes
What is the inverse equation of 3(x-1)^2+6 ?

1 Answer

1 vote

Answer:

Correct answer: y = √(x - 6)/3 + 1

Explanation:

Given:

y = 3 (x - 1)² + 6

I suppose you meant an inverse function and not an equation.

One way to get an inverse function is to solve it by x.

Let's do it

y = 3 (x - 1)² + 6 ⇒ 3 (x - 1)² = y - 6 ⇒ (x - 1)² = (y - 6) / 3 ⇒

x - 1 = √(y - 6) / 3 ⇒ x = √(y - 6) / 3 + 1

x = √(y - 6) / 3 + 1 Finally, we switch roles to x and y

y = √(x - 6) / 3 + 1

God is with you!!!

User Bartlomiej
by
4.5k points